Chemical and volatile composition, and microbial communities in edible purple flowers (Torenia fournieri F. Lind.) cultivated in different organic systems - Santos de Morais, Janne; Cabral, Lucélia; Karoline Almeida da Costa, Whyara; Osmari Uhlmann, Lilian; dos Santos Lima, Marcos; Fontes Noronha, Melline; Alves dos Santos, Silvana; Suely Madruga, Marta; Souza Olegario, Lary; Wagner, Roger; Sant'Ana, Anderson S.; Magnani, Marciane (Elsevier, 2022)
Edible flowers have been widely consumed fresh in drinks, salads, desserts and salty dishes. This study evaluated the color parameters, chemical composition (phenolics, sugars, organic acids), volatiles compounds and microbiota (bacterial and fungal communities) in edible purple flowers (Torenia fournieri F. Lind.) cultivated in biocompost and traditional organic systems. Torenia flowers cultivated in biocompost had high (p < 0.05) contents of anthocyanins (cyanidin 3,5-diglucoside, delphinidin 3-glucoside), flavonols (quercitin 3-glycoside, myricetin and rutin), sugars (rhamnose and glucose), organic acids (citric and succinic), aldehydes (hexanal, cis-2-hexenal and trans-2-hexenal), and alcohols (trans-2-hexenol and 3-ethyl-4-methylpentan-1-ol). Flowers cultivated in biocompost showed higher (p < 0.05) abundance Cyanobacteria and Basidiomycota bacterial and fungal phyla, respectively, than flowers cultivated in traditional system. The high abundance of Oxyphotobacteria and Dothideomycetes classes, Acetobacterales and Cladosporiales orders, Oxyphotobacteriaceae and Cladosporiaceae families, and Raoultella and Cladosporium genera characterized torenia flowers cultivated in biocompost. The cultivation system influenced the torenia flowers microbiota and composition, primarily due to environmental response and enhanced uptake of nutrients. Our findings indicate that cultivation of torenia using the agroindustrial based-biocompost improves bioactive and volatiles contents in more purple and fruity flavored flowers, rendering flowers more attractive for consumption.
Keywords: Agro-industrial residues; Anthocyanin; Edible flowers; Flavor compounds; Microbiota; Organic cultivation